Financial Sector Assessment : Algeria - World Bank (Washington, DC, 2013)
Over the past decade, Algeria has courageously attempted to modernize its financial system, despite social strife, and unique challenges posed by the large hydrocarbon sector. However, lending by state-owned banks, mostly to public entities, still dominates financial intermediation, financial markets remain in their infancy, and, implementation of regulatory reforms is lagging. And, because of hydrocarbon-funded state support to borrowers and lenders alike, the financial system appears stable, although this "stability" carries high costs, and distorts risk pricing and governance. The report emphasizes that to alter these patterns, the authorities should push on several, mutually reinforcing policy fronts: privatization of all public banks over the medium term; improvements in the banking system, namely banking operations, to cut intermediation costs; stimulate a strong institutional framework, and regulation of hydrocarbon-induced liquidity and credit cycles, that curtail banks' risk-taking; and, undertake longer-term reforms to stimulate the non-bank financial sector. Nevertheless, the report also stipulates that privatization should not attempt to recoup past budgetary outlays, but prevent future ones, and let new owners decide on investments, and cost cuts. Direct budgetary support should replace lending to non-viable State-owned enterprises (SOEs) and financial support to public programs, such as housing or agriculture. Instead, the government should consider replacing the current guarantee subsidies, with direct budgetary financing of public entities, whereas in managing their housing and agriculture finance programs, the authorities should consider alternative methods. Banking supervision, and prudential regulation need strengthening in many core areas. The Bank of Algeria (BA) as supervisor, can play a useful role in the operational restructuring of public banks by enforcing regulation to gain a firm handle on bank profitability. But, while the ordinance on Money and Credit of October 2003 contain some improvements, other provisions could undermine BA's financial, and operational autonomy. Financial system stability and development in Algeria, have strong overtones of public debt, and expenditure management, because of the policies that regulate the effects of the oil cycle on bank liquidity, and credit risks.